Efektivitas Penggunaan SAP dalam Pencatatan Transaksi Keuangan : Pengalaman Magang di PT Pos Indonesia Regional V Surabaya - Dela Wahyu Putri Awanda; Uhti Noer Choliza Safitri; Devina Shava Amalia; Ataina Rusyda Fauziyah (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This article discusses the four-month internship experience at PT Pos Indonesia Regional V Surabaya, specifically in the Finance and Accounting section, with a focus on evaluating the effectiveness of using the SAP S/4HANA system in recording financial transactions. The research used a descriptive qualitative approach with a literature study method that was analyzed thematically. The results showed that SAP supports real-time transaction recording, is integrated between modules, has an adequate audit trail, and increases HR competence in terms of accuracy and work efficiency. The conclusion shows that the SAP system has proven effective in supporting operational efficiency and internal control of the company, while providing practical experience and important learning for students in facing the digital and integrated world of work.